2012
DOI: 10.1080/10643389.2011.574115
|View full text |Cite
|
Sign up to set email alerts
|

Biochar: Carbon Sequestration, Land Remediation, and Impacts on Soil Microbiology

Abstract: Biochar -charcoal used to amend land and sequester carbon -is attracting considerable interest. Its distinctive physical/chemical/biological properties, including high water-holding capacity, large surface area, cation exchange capacity, elemental composition and pore size/volume/distribution, effect its recognised impacts, especially on microbial communities. These are explored in the context of agriculture, composting and land remediation/restoration. Considerable focus is given to mycorrhizal associations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(70 citation statements)
references
References 265 publications
0
56
0
3
Order By: Relevance
“…Similar increases were estimated in case of potassium. Thanks to the well-known porosity and high surface area properties of biochar its application could potentially act both as a kind of storage facility and source of these important elements, and to increase the soil water retention capacity [26], while reducing soil acidity due to its alkaline properties. With further study and the determination of additional characteristics, such as the effect of torrefacton on the availability of major nutrients and contaminants, water retention and plant growth inhibition, this approach could provide the necessary assurances for the recovery of various organic wastes and the inclusion of biochar in the list of common soil amendments for agricultural use as part of the EU's biobased Circular Economy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar increases were estimated in case of potassium. Thanks to the well-known porosity and high surface area properties of biochar its application could potentially act both as a kind of storage facility and source of these important elements, and to increase the soil water retention capacity [26], while reducing soil acidity due to its alkaline properties. With further study and the determination of additional characteristics, such as the effect of torrefacton on the availability of major nutrients and contaminants, water retention and plant growth inhibition, this approach could provide the necessary assurances for the recovery of various organic wastes and the inclusion of biochar in the list of common soil amendments for agricultural use as part of the EU's biobased Circular Economy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have pointed out the refuge for microorganisms provided by biochar porosity (Lehmann et al, 2011;Ennis et al, 2012), while others have also suggested the increased nutrient and carbon availability and water retention around biochar, the sorption of noxious chemicals, and the increased pH in the specific case of acid soils (Lehmann et al, 2011). On the other hand, Pietikäinen et al (2000) proposed the reduction of microbial cell leaching by direct retention in biochar as explanation.…”
Section: Introductionmentioning
confidence: 95%
“…Char Char has received increasing attention due to its suitability for several applications (Nanda et al 2016;Qian et al 2015;Xie et al 2015), which include the use as a solid fuel (Lohri et al 2016), soil amendment (bio-char) (Ennis et al 2012;Lehmann et al 2011;Tang et al 2013;Xu et al 2012), or precursor for making catalysts and contaminant adsorbents (Inyang and Dickenson 2015;Manyà 2012;Mohan et al 2014;Tan et al 2015). As discussed above, the feedstock type and pyrolysis operating conditions influences the physical, chemical, and mechanical properties of chars which in turn have an effect on the potential to utilize char for the various applications (Kan et al 2016;Qian et al 2015).…”
Section: Products and Usesmentioning
confidence: 99%